The Opioid Epidemic: Can We Reverse The Historical Trend? - Donald J Schroeder (Journal of Addiction Medicine and Therapeutic Science - Peertechz Publications, 2018)
Opium derived from the condensed juice of the poppy, Papaver Somniferum, has been used as an analgesic, euphoric, and soporific for centuries. The use of opium use goes back 6000 years to China. It was initially cultivated in 3400 B.C. in Mesopotamia, and has been used therapeutically and recreationally ever since. In fact, opium was available during the time of Hippocrates, the father of medicine (circa 470-370 B.C.). In 1660 A.D., the English physician, Thomas Sydenham, compounded an opium tincture, which he called Laudanum. This was considered the medicinal "cure all" for most ailments. Numerous scientists have experimented since then by mixing opium with other agents including whiskey, rum, brandy, ether, and chloroform. Laudanum is now virtually extinct in the U.S., though still can be obtained in a number of European countries.